2022
DOI: 10.55563/clinexprheumatol/o5t1f7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyclophosphamide and rituximab in patients with connective tissue diseases with severe interstitial lung disease

Abstract: ObjectiveWe aimed to analyse the effects of real-life immunomodulatory therapy with cyclophosphamide and rituximab for interstitial lung disease (ILD) in patients with systemic sclerosis (SSc-ILD), anti-synthetase syndrome (ASS-ILD), or Sjögren's syndrome (SjS-ILD), in a single academic centre. Methods All inpatients with connective tissue diseases treated with intravenous bolus cyclophosphamide or rituximab were identified from the Medical Centre records. Information on patient characteristics, chest CT resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Huapaya et al (38) showed no difference in FVC% and DLCO% between patients treated and those not treated with mycophenolate mofetil (MMF). Benad et al (39) showed that cyclophosphamide and/or rituximab led to improvement of FVC% in 12 patients, and stabilisation in 14 out of 27 severely sick patients with ILD associated with systemic sclerosis, antisynthetase syndrome and Sjögren's syndrome. In our survival and mixed model analysis of FVC% and DLCO%, there was no difference over time, even after adjusting the models for the prior use of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Huapaya et al (38) showed no difference in FVC% and DLCO% between patients treated and those not treated with mycophenolate mofetil (MMF). Benad et al (39) showed that cyclophosphamide and/or rituximab led to improvement of FVC% in 12 patients, and stabilisation in 14 out of 27 severely sick patients with ILD associated with systemic sclerosis, antisynthetase syndrome and Sjögren's syndrome. In our survival and mixed model analysis of FVC% and DLCO%, there was no difference over time, even after adjusting the models for the prior use of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside data on the proven efficacy of "classic" immunosuppressants such as cyclophosphamide and rituximab, which consolidate their use in the treatment of SSc-ILD (48), in the last year the focus has been mainly on tocilizumab (TCZ). After two randomised controlled trials (RCTs), namely faSScinate and focuSSced, showed a trend in improvement of skin fibrosis and in prevention of lung function worsening in a highly enriched population of patients with early, inflammatory, diffuse and progressive SSc, the most suitable field of application for this anti-IL-6 receptor antibody has been investigated.…”
Section: Immunosuppressive Therapiesmentioning
confidence: 99%
“…Among the therapy, azathioprine [79,216] and mycophenolate mofetil [217,218] have been reported. Biologic therapy, such as rituximab, a humanized monoclonal antibody targeting mature B-cells (CD20+), was tried in case series and reports with promising results [219], in reparatory cases [220] and also associated with lymphoproliferative diseases [221][222][223], in special cases, such as in shrinking lung syndrome associated with SS [224]. Off-the-label cases reported other biologicals, such as tocilizumab [225] and abatacept [226].…”
Section: Brief Historymentioning
confidence: 99%